2015
DOI: 10.1016/j.spl.2015.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Elicitable distortion risk measures: A concise proof

Abstract: Elicitability has recently been discussed as a desirable property for risk measures. Kou and Peng (2014) showed that an elicitable distortion risk measure is either a Value-at-Risk or the mean. We give a concise alternative proof of this result, and discuss the conflict between comonotonic additivity and elicitability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 16 publications
(18 reference statements)
0
11
0
Order By: Relevance
“…In the literature of risk measures, many results on the characterization of elicitable risk measures are obtained via characterizing the CxLS property in dimension one; see Weber (2006), Bellini and Bignozzi (2015), and Delbaen, Bellini, Bignozzi, and Ziegel (2016) for convex risk measures, Ziegel (2016) for coherent risk measures, Kou and Peng (2016) and Wang and Ziegel (2015) for distortion risk measures, Liu and Wang (2020) for tail risk measures, and Fissler, Hlavinová, and Rudloff (2019a, b) for set‐valued risk functionals. As far as we are aware of, studies dedicated to CxLS in the multidimensional setting are not found in the literature, although multidimensional elicitability has been a popular topic; see Lambert, Pennock, and Shoham (2008), Fissler and Ziegel (2016), Nolde and Ziegel (2017), and Acerbi and Szekely (2017) for multidimensional elicitability and their statistical implications.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature of risk measures, many results on the characterization of elicitable risk measures are obtained via characterizing the CxLS property in dimension one; see Weber (2006), Bellini and Bignozzi (2015), and Delbaen, Bellini, Bignozzi, and Ziegel (2016) for convex risk measures, Ziegel (2016) for coherent risk measures, Kou and Peng (2016) and Wang and Ziegel (2015) for distortion risk measures, Liu and Wang (2020) for tail risk measures, and Fissler, Hlavinová, and Rudloff (2019a, b) for set‐valued risk functionals. As far as we are aware of, studies dedicated to CxLS in the multidimensional setting are not found in the literature, although multidimensional elicitability has been a popular topic; see Lambert, Pennock, and Shoham (2008), Fissler and Ziegel (2016), Nolde and Ziegel (2017), and Acerbi and Szekely (2017) for multidimensional elicitability and their statistical implications.…”
Section: Introductionmentioning
confidence: 99%
“…Among the many papers on these utility functions, we could refer the reader to the cited papers and to e.g. Bellini et al [3], Bellini et al [4], Wang and Ziegel [19], Weber [20] and Ziegel [22].…”
Section: Introduction and Notationmentioning
confidence: 99%
“…It is also examined in a purely mathematical framework in [34]. The elicitability of risk measures is further analyzed in [3] and [35]. Expectiles, as risk measures, were the subject of the works presented in [16], [5], and [4].…”
Section: Introductionmentioning
confidence: 99%